A Cytotoxic, Co-operative Interaction Between Energy Deprivation and Glutamate Release From System xc− Mediates Aglycemic Neuronal Cell Death. (3rd November 2015) - Thorn, Trista L.; He, Yan; Jackman, Nicole A.; Lobner, Doug; Hewett, James A.; Hewett, Sandra J.
The astrocyte cystine/glutamate antiporter (system xc − ) contributes substantially to the excitotoxic neuronal cell death facilitated by glucose deprivation. The purpose of this study was to determine the mechanism by which this occurred. Using pure astrocyte cultures, as well as, mixed cortical cell cultures containing both neurons and astrocytes, we found that neither an enhancement in system xc − expression nor activity underlies the excitotoxic effects of aglycemia. In addition, using three separate bioassays, we demonstrate no change in the ability of glucose-deprived astrocytes—either cultured alone or with neurons—to remove glutamate from the extracellular space. Instead, we demonstrate that glucose-deprived cultures are 2 to 3 times more sensitive to the killing effects of glutamate or N -methyl-D-aspartate when compared with their glucose-containing controls. Hence, our results are consistent with the weak excitotoxic hypothesis such that a bioenergetic deficiency, which is measureable in our mixed but not astrocyte cultures, allows normally innocuous concentrations of glutamate to become excitotoxic. Adding to the burgeoning literature detailing the contribution of astrocytes to neuronal injury, we conclude that under our experimental paradigm, a cytotoxic, co-operative interaction between energy deprivation and glutamate release from astrocyte system xc − mediates aglycemic neuronal cell death.